Konservatisme Akuntansi: Faktor Financial Distress, Intensitas Modal, Dan Debt Covenant - Erwin Indriyanto; Tia Dwi Cahyani (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aims to empirically test and analyze the effect of Financial Distress, Capital Intensity, and Debt Covenant on Accounting Conservatism. The data source of this research uses secondary data in the form of annual reports on mining industry sector companies listed on the Indonesia Stock Exchange in 2016-2020. The method used to determine the sample is purposive sampling, so that the sample used is 75 mining companies. Hypothesis testing was carried out with multiple linear regression using SPSS version 26.0. Study’s result indicate that the factors that have a significant effect on accounting conservatism are financial distress and debt covenants. While the capital intensity factor has no significant effect on accounting conservatism. These results can be an insight and reference for investors in seeing future prospects in the mining sector. In addition, for actors in the mining sector to be more careful in implementing accounting conservatism.